1989
DOI: 10.1128/aac.33.9.1531
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activities of clarithromycin against Mycobacterium avium

Abstract: There is no effective therapy to treat Mycobacterium avium complex infection in patients with acquired immune deficiency syndrome. Clarithromycin (A-56268; TE-031) is a new macrolide which is twofold more active than erythromycin against most aerobic bacteria. In addition, higher levels in serum and tissue are achieved with clarithromycin than with erythromycin. In this study, clarithromycin, erythromycin, difloxacin, temafloxacin, ciprofioxacin, rifampin, amikacin, and ethambutol were tested in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 9 publications
4
86
1
2
Order By: Relevance
“…This hypothesis presupposes that impermeability is the mechanism of resistance to clarithromycin in M. tuberculosis. This may not be the case, since clarithromycin apparently penetrates the cell envelope of other mycobacteria to a degree sufficient to cause inhibition (1,3,4,8,23).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This hypothesis presupposes that impermeability is the mechanism of resistance to clarithromycin in M. tuberculosis. This may not be the case, since clarithromycin apparently penetrates the cell envelope of other mycobacteria to a degree sufficient to cause inhibition (1,3,4,8,23).…”
Section: Discussionmentioning
confidence: 95%
“…Clarithromycin is a new macrolide antibiotic which achieves good concentrations in the respiratory tract, is orally administered, and has been shown to have antimycobacterial activity (1,3,4,8,11,23). These facts led us to Clarithromycin and its metabolite, either alone or in combination, had very little activity against multidrug-resistant M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy resorts to a combination of several drugs and, as in tuberculosis, is very lengthy. Long-term treatment with macrolides such as clarithromycin, which is highly effective in the treatment of MAC infections (4,5), leads to the emergence of resistant forms (6 -8), which can be prevented by combining at least two or three drugs (9,10). However, this in turn can lead to severe side effects (11,12).…”
mentioning
confidence: 99%
“…There could be scope further improve survival by better management of comorbid conditions and by improving the general health of the patient. It may be that macrolides and/or quinolones, which, during the period of this study, were found to have in vitro activity against opportunist mycobacteria [14][15][16][17][18], will result in better cure rates when added to rifampicin and ethambutol. The British Thoracic Society9s ongoing multicentre trial should answer this question by the end of 2004.…”
Section: Discussionmentioning
confidence: 99%